Charity from Afar: The Ioannina Foundations of the Greek Communities of Vienna (1769–1914) - Saracino, Stefano (The Historical Review/La Revue Historique, 2019)
This article analyses eight charitable foundations established by persons from Ioannina between the 1780s and 1800s for the benefit of their home town that were administered by the two Greek Orthodox communities of Vienna. All of the endowments were based on large capital sums deposited in Viennese financial institutions, such as the Wiener Stadtbank, whose revenues were used for manifold charitable ends. The article reconstructs the wills and motivations of the founders, as well as the administrative/operative structures of their endowments, which were in existence up to 1914, when they fell victim to the hyperinflation of the following years. Whereas endowment historians usually focus on the founders’ wills and establishment of endowments, research on their everyday operation over the long term is seldom. Furthermore, the present study proposes an approach to charitable foundations that focuses on their cultural, confessional, social and economic importance for migrant groups.